Positive electrode active material for lithium secondary battery and lithium secondary battery comprising same
By doping strontium and sulfur into the positive electrode active substance of the lithium secondary battery, lithium transition metal oxides containing nickel, cobalt and manganese are formed, which solves the problem of degradation of the repeated charge/discharge stability and life characteristics of the lithium secondary battery, and achieves a balance of high capacity, economy and stability.
Patent Information
- Application Number
- CN202411193584.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-04
- Filing Date
- 2024-08-28
- Publication Date
- 2025-03-04
AI Technical Summary
The stability and life characteristics of lithium secondary batteries decrease when they are repeatedly charged and discharged, and the increase in nickel content leads to instability in the chemical structure and crystal structure of the positive electrode active substance.
A lithium transition metal oxide containing nickel, cobalt, manganese, strontium and sulfur is used as the positive electrode active material. The molar fraction of nickel is set to be 0.9 or more, the molar ratio of cobalt to manganese is between 0.9 and 1.5, and the molar ratio of strontium to sulfur is between 0 and 4, so as to improve the conductivity and stability of the positive electrode active material.
By doping strontium and sulfur, oxygen detachment and oxygen generation are suppressed, and the repeated charge/discharge stability and life characteristics of lithium secondary batteries are improved, while ensuring high capacity and economy.
Smart Images

Figure CN119560554A_ABST
Abstract
Description
Technical Field
[0001] The disclosure of the present application relates to a positive electrode active material for a lithium secondary battery and a lithium secondary battery comprising the same, and more specifically, to a positive electrode active material for a lithium secondary battery containing cobalt and manganese and a lithium secondary battery comprising the same. Background Art
[0002] Secondary batteries are batteries that can be repeatedly charged and discharged. With the development of the information communication and display industries, they are widely used as power sources for portable electronic communication devices such as camcorders, mobile phones, and notebook computers. In addition, battery packs including secondary batteries have recently been developed and used as power sources for environmentally friendly vehicles such as electric cars.
[0003] Examples of secondary batteries include lithium secondary batteries, nickel-cadmium batteries, and nickel-metal hydride batteries. Among them, lithium secondary batteries have been actively researched and developed because of their high operating voltage and energy density per unit weight, and advantages such as high charging speed and light weight.
[0004] NCM-based active materials containing nickel, cobalt, and manganese are being used as positive electrode active materials for lithium secondary batteries. As the application range of lithium secondary batteries expands to large-scale equipment such as electric vehicles, high-nickel (High-Ni) lithium oxides with increased nickel content are being developed as positive electrode active materials to ensure high capacity of lithium secondary batteries. However, as the nickel content in the positive electrode active material increases, the stability of the chemical structure and crystal structure of the active material particles may decrease.
[0005] For example, due to the cation mixing phenomenon caused by the transfer of nickel cations to lithium sites, the stability and life characteristics of lithium secondary batteries may be reduced when charging / discharging operations are repeated.
[0006] In addition, as the nickel content increases, the content of cobalt and manganese contained in the positive electrode active material can be relatively reduced. It is necessary to design a positive electrode active material composition that can ensure the economical production of the positive electrode active material and provide sufficient conductivity and stability. Summary of the invention
[0007] Technical issues
[0008] An object of the present disclosure is to provide a positive electrode active material for a lithium secondary battery having improved stability and charge / discharge characteristics.
[0009] An object of the present disclosure is to provide a lithium secondary battery including the above-mentioned positive electrode active material.
[0010] Technical Solution
[0011] The positive electrode active material for a lithium secondary battery includes a lithium transition metal oxide containing nickel (Ni), cobalt (Co), manganese (Mn), strontium (Sr), and sulfur (S). In the above lithium transition metal oxide, the molar fraction of nickel in the total molar amount of nickel, cobalt, and manganese is 0.9 or more, the molar ratio of cobalt to manganese in the above lithium transition metal oxide is 0.9 to 1.5, and the molar ratio of strontium (Sr) to sulfur (S) in the above lithium transition metal oxide is greater than 0 and 4 or less.
[0012] In some embodiments, in the above lithium transition metal oxide, the molar ratio of cobalt to manganese may be 1 to 1.5.
[0013] In some embodiments, in the above lithium transition metal oxide, the molar ratio of strontium (Sr) to sulfur (S) may be 0.1 to 3.
[0014] In some embodiments, in the above lithium transition metal oxide, the content of nickel among the elements other than lithium and oxygen may be 90% or more.
[0015] In some embodiments, the above lithium transition metal oxide may further contain Al.
[0016] In some embodiments, in the total weight of the above lithium transition metal oxide, the content of Al may be 1000 ppm to 10000 ppm.
[0017] In some embodiments, the above lithium transition metal oxide may include a layered structure or a crystal structure represented by Chemical Formula 1.
[0018] [Chemical Formula 1]
[0019] Li a Sr b (Ni x M1 1-x) M2 y O 2-z S z
[0020] In Chemical Formula 1, 0.95 ≤ a + b ≤ 1.1, 0 < b ≤ 0.1, 0.9 ≤ x < 1.0, 0 ≤ y ≤ 0.1, 0 < z ≤ 0.1. M1 includes Co and Mn, and M2 is a foreign metal other than Ni, Co, Mn, and Sr.
[0021] In some embodiments, M2 may include at least one selected from Al, Rb, Y, Zr, Nb, Mo, Ru, Ag, Sn, and Sb.
[0022] A lithium secondary battery includes a positive electrode and a negative electrode opposite to the positive electrode. The positive electrode includes the positive electrode active material for a lithium secondary battery according to the above embodiments. The negative electrode includes a negative electrode active material, and the negative electrode active material includes a carbon-based active material and a silicon-based active material.
[0023] In some embodiments, the weight ratio of silicon element in the total weight of carbon element (C) and silicon element (Si) contained in the negative electrode active material may be 1% to 10%.
[0024] In some embodiments, the weight ratio of silicon element in the total weight of carbon element (C) and silicon element (Si) contained in the negative electrode active material may be 1% to 7%.
[0025] In some embodiments, the carbon-based active material may include natural graphite or artificial graphite.
[0026] Technical Effects
[0027] According to the positive electrode active material for a lithium secondary battery according to an embodiment of the present disclosure, strontium (Sr) and sulfur (S) may be doped or combined in the chemical structure or crystal structure of the lithium transition metal oxide.
[0028] Sulfur atoms can be substituted or doped into oxygen (O) sites in the chemical structure or crystal structure of the lithium transition metal oxide, thereby suppressing the release of oxygen and the generation of oxygen gas that occur when the secondary battery is repeatedly charged / discharged.
[0029] Sr has a +2 ion state, and Sr ions may have a larger ion radius than lithium ions and nickel ions. Therefore, Sr can effectively inhibit the occurrence of cation mixing of nickel ions and promote S doping.
[0030] The lithium transition metal oxide contains cobalt and manganese, and the molar fraction of nickel may be greater than 80%. In the lithium transition metal oxide, the molar ratio of cobalt to manganese is maintained within a predetermined range, thereby ensuring the conductivity and stability of the positive electrode active material.
[0031] According to an exemplary embodiment, the lithium secondary battery may include the positive electrode active material and a silicon-based negative electrode active material. The silicon content in the silicon-based negative electrode active material is maintained within a predetermined range, so that a balance between discharge capacity / power and high temperature stability can also be achieved in the negative electrode.
[0032] According to exemplary embodiments, lithium secondary batteries can be widely used in the field of green technology, including electric vehicles, battery charging stations, solar power generation using batteries, wind power generation, etc. For example, the above lithium secondary batteries are applied to eco-friendly electric vehicles, hybrid vehicles, etc., which can suppress air pollution and greenhouse gas emissions and prevent climate change. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 and Figure 2are respectively a schematic plan view and a cross-sectional view of a lithium secondary battery according to an exemplary embodiment;
[0034] Figure 3 It is a Differential Scanning Calorimetry (DSC) analysis chart of the positive electrode active material particles of Examples 1 and 2 and Comparative Example 1. DETAILED DESCRIPTION
[0035] Embodiments of the present disclosure provide a positive electrode active material for a lithium secondary battery, which contains nickel, cobalt and manganese and has a doping element. In addition, a lithium secondary battery is provided, which includes the positive electrode active material and has improved capacity, efficiency and stability.
[0036] The following will describe the embodiments of the present disclosure in more detail. However, the drawings and embodiments of this specification serve to help further understand the technical ideas of the present disclosure, so the concept of the present invention should not be limited to the matters recorded in the above drawings and embodiments.
[0037] <Positive electrode active material for lithium secondary battery>
[0038] In an exemplary embodiment, a positive electrode active material for a lithium secondary battery (hereinafter may be simply referred to as a "positive electrode active material") may include a lithium transition metal oxide. The positive electrode active material may include a plurality of lithium transition metal oxide particles.
[0039] For example, the content of the lithium transition metal oxide particles in the total weight of the positive electrode active material may be 50 wt % or more, or 70 wt % or more, 80 wt % or more, 90 wt % or more, or 95 wt %.
[0040] In one embodiment, the positive electrode active material may further include other NCM-based active materials, cobalt-free (Co-less) series active materials, over-lithiated oxide (OLO)-based active materials, lithium iron phosphate-based active materials, etc. in addition to the lithium transition metal oxide particles described later.
[0041] In one embodiment, the positive electrode active material may be substantially composed of the lithium transition metal oxide particles.
[0042] The lithium transition metal oxide may contain nickel (Ni), cobalt (Co) and manganese (Mn). Co and Mn may serve as main active elements of the positive electrode active material together with Ni.
[0043] According to an embodiment of the present disclosure, the molar fraction of nickel in the elements other than lithium and oxygen contained in the lithium transition metal oxide may be greater than 0.8. For example, the molar ratio of nickel in the total molar number of nickel, cobalt and manganese contained in the lithium transition metal oxide may be greater than 0.8.
[0044] In some embodiments, the molar fraction of nickel may be greater than 0.85, greater than 0.88, greater than 0.9, greater than 0.91, greater than 0.92, greater than 0.945, or greater than 0.95.
[0045] In one embodiment, to ensure high capacity, the molar fraction of nickel may be adjusted to be above 0.9.
[0046] In some embodiments, the content of nickel in the elements other than lithium and oxygen in the lithium transition metal oxide can reach more than 90 weight %.
[0047] According to an embodiment of the present disclosure, a molar ratio of cobalt to manganese (hereinafter may be represented as Co / Mn) contained in the lithium transition metal oxide may be 0.9 to 1.5.
[0048] For example, when Co / Mn is less than 0.9, the conductivity of the positive electrode active material is excessively reduced, which may lead to a decrease in the power of the secondary battery, and a decrease in Co may lead to a collapse of the layered structure and a decrease in thermal stability.
[0049] When Co / Mn exceeds 1.5, the content of relatively high-cost Co increases, which may reduce the overall economic efficiency of the secondary battery. In addition, since the content of Mn is not sufficiently ensured, instability may be caused by introducing a high-nickel (High-Ni) composition.
[0050] In one embodiment, Co / Mn is 1 to 1.5. In one embodiment, more preferably, it may be greater than 1 and less than 1.5. In one embodiment, or it may be greater than 1 and less than 1.5. Within the above range, the layered structure of the lithium transition metal oxide can be effectively prevented from collapsing, and the active material particles can be prevented from cracking.
[0051] According to an embodiment of the present disclosure, the lithium transition metal oxide may further contain strontium (Sr) and sulfur (S) in the chemical structure or crystal structure. For example, strontium (Sr) and sulfur (S) may exist in the lithium transition metal oxide in a doped form.
[0052] According to an exemplary embodiment, strontium (Sr) may be substituted to a lithium site in a chemical structure or a crystal structure of the lithium transition metal oxide. Sulfur (S) may be substituted to an oxygen (O) site in a chemical structure or a crystal structure of the lithium transition metal oxide.
[0053] As sulfur atoms or sulfur ions are partially substituted to oxygen sites, the desorption of oxygen and the generation of oxygen (O2) due to side reactions can be suppressed or reduced.
[0054] For example, with the introduction of high-nickel (High-Ni) composition, the chemical instability of the surface of the positive active material may increase and easily lead to side reactions with the electrolyte. For example, when the positive active material is exposed to a high temperature environment, oxygen is generated through the above side reactions, which can cause battery expansion and explosion.
[0055] According to the embodiments of the present disclosure, some oxygen sites can be replaced by doping sulfur components. Sulfur ions have a larger ion radius than oxygen ions and are not easy to break away from the crystal structure, which can enhance the crystal stability of lithium transition metal oxides.
[0056] For example, Sr and S can be introduced together through a source such as SrSO4 when preparing lithium transition metal oxides or positive electrode active materials. Sr is substituted into lithium sites and has a larger ionic radius than lithium ions, so it can change the oxygen-oxygen bonding angle in the crystal structure.
[0057] Therefore, the repulsive force with the adjacent oxygen (O) can be reduced when sulfur (S) is substituted or doped, while promoting the introduction of sulfur (S). Therefore, sulfur doping can be stably achieved without causing excessive damage / deformation of the crystal structure of the lithium transition metal oxide.
[0058] Furthermore, Sr has an oxidation number of +2, and Li has an oxidation number of +1. Therefore, Sr can be substituted to two lithium sites, and the repulsive force between S and Li generated when sulfur is doped can also be reduced. Therefore, sulfur doping can be performed more easily.
[0059] Strontium (Sr) includes a d-orbital, has an ionic radius larger than that of lithium ions, and may have an ionic radius larger than that of nickel ions. Therefore, cation mixing that occurs when nickel elements or nickel ions are transferred to lithium sites may be alleviated or suppressed. For example, strontium (Sr) may be provided as a blocking element for nickel ion transfer.
[0060] According to an embodiment of the present disclosure, the molar ratio of strontium (Sr) to sulfur (S) in the lithium transition metal oxide (hereinafter, may also be expressed as Sr / S) may be greater than 0 and less than 4. When Sr / S exceeds 4, excessive Sr substitution may cause a decrease in capacity and power, and may cause deformation of the crystal structure / layered structure. In addition, the effect of reducing oxygen brought about by doping S may not be substantially achieved.
[0061] In some embodiments, Sr / S may be 0.1 to 3 or 0.2 to 2.5. Within the above range, the generation of gas may be more effectively suppressed while ensuring high temperature life characteristics.
[0062] As described above, by adjusting Co / Mn and Sr / S together to the ratios of the embodiments of the present disclosure, the thermal stability and high-temperature life characteristics of the positive electrode active material can be improved simultaneously, inducing a mutual synergistic effect.
[0063] In some embodiments, the above positive electrode active material or lithium transition metal oxide may further include additional doping or coating elements. For example, the above doping or coating elements may be present on the surface of the above lithium transition metal oxide particles, or penetrate through the surface of the above lithium transition metal oxide particles and be included in the binding structure represented by Chemical Formula 1 or Chemical Formula 1-1.
[0064] In some embodiments, the above lithium transition metal oxide may include a layered structure or a crystal structure represented by Chemical Formula 1.
[0065] [Chemical Formula 1]
[0066] Li a Sr b (Ni x M1 1-x) M2 y O 2-z S z
[0067] In Chemical Formula 1, 0.95 ≤ a + b ≤ 1.1, 0 < b ≤ 0.1, 0.9 ≤ x < 1.0, 0 ≤ y ≤ 0.1, 0 < z ≤ 0.1. M1 includes Co and Mn, and M2 may be a foreign metal other than Ni, Co, Mn, and Sr.
[0068] In one embodiment, in Chemical Formula 1, 0 < b ≤ 0.05, 0 ≤ y < 0.05, 0 < z < 0.05.
[0069] In one embodiment, in Chemical Formula 1, 0 < b ≤ 0.005, 0 ≤ y < 0.05, 0 < z < 0.005.
[0070] As described above, in Chemical Formula 1, 0.9 ≤ Co / Mn ≤ 1.5. M2 may include at least one selected from Al, Rb, Y, Zr, Nb, Mo, Ru, Ag, Sn, and Sb. In one embodiment, M2 may include Al.
[0071] In some embodiments, the positive electrode active material or the lithium transition metal oxide may contain Al in the range of 1000ppm to 10000ppm. When Al in the above content range is included, the capacity retention characteristics and the gas generation inhibition characteristics can be further enhanced. In one embodiment, the content of Al can be 1500ppm to 8000ppm or 2000ppm to 7000ppm of the total weight of the lithium transition metal oxide.
[0072] The chemical structure shown in Chemical Formula 1 represents the bonding relationship contained in the layered structure or crystal structure of the positive electrode active material, and does not exclude other additional elements. For example, M1 includes Co and / or Mn, and Co and Mn can be provided together with Ni as the main active elements of the positive electrode active material. Chemical Formula 1 is provided to represent the bonding relationship of the above-mentioned main active elements, and should be understood as a formula including the introduction and substitution of additional elements.
[0073] In one embodiment, an auxiliary element may be added to the main active element to enhance the chemical stability of the positive electrode active material or the layered structure / crystal structure. The auxiliary element may be mixed into the layered structure / crystal structure to form a bond, and it should be understood that this situation is also included in the chemical structure represented by Chemical Formula 1.
[0074] The auxiliary elements may include Na, Mg, Ca, Ti, Hf, V, Ta, Cr, W, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Ba, Ra, P, etc. The auxiliary elements may be provided as the additional doping / coating elements.
[0075] The following provides a method for preparing a positive electrode active material according to the above-mentioned embodiment of the present disclosure.
[0076] According to an exemplary embodiment, an active material metal source may be prepared, and the active material metal source may include a nickel source, a manganese source, and a cobalt source.
[0077] Examples of the above-mentioned nickel source include nickel sulfate (NiSO4), nickel hydroxide (Ni(OH)2), nickel nitrate (Ni(NO3)2), nickel acetate (Ni(CH3CO2)2), and hydrates thereof. Examples of the above-mentioned manganese source include manganese sulfate (MnSO4), manganese hydroxide (Mn(OH)2), manganese nitrate (Mn(NO3)2), manganese acetate (Mn(CH3CO2)2), and hydrates thereof. Examples of the above-mentioned cobalt source include cobalt sulfate (CoSO4), cobalt hydroxide (Co(OH)2), cobalt nitrate (Co(NO3)2), cobalt carbonate (CoCO3), and hydrates thereof.
[0078] In one embodiment, nickel sulfate, manganese sulfate, and cobalt sulfate may be used as the nickel source, the manganese source, and the cobalt source, respectively.
[0079] According to an exemplary embodiment, the active material precursor may be obtained by mixing the active material metal sources and reacting them, for example, by a coprecipitation method. For example, the active material precursor may be prepared in the form of nickel-manganese-cobalt hydroxide.
[0080] In order to promote the above coprecipitation reaction, a precipitant and / or a chelating agent may be used, and the above precipitant may include alkaline compounds such as sodium hydroxide (NaOH) and sodium carbonate (Na2CO3). The above chelating agent may include, for example, ammonia water, ammonium carbonate, etc.
[0081] The active material precursor may be mixed with a strontium source and a lithium source, and reacted by heat treatment to prepare lithium transition metal oxide particles. For example, the heat treatment temperature may be about 600 to 850°C.
[0082] The strontium source may include, for example, strontium carbonate (SrCO3), strontium sulfate (SrSO4), etc. In one embodiment, strontium sulfate (SrSO4) may be used.
[0083] The lithium source may include, for example, lithium carbonate (Li2CO3), lithium nitrate (LiNO3), lithium acetate (CH3COOLi), lithium oxide (Li2O), lithium hydroxide (LiOH), etc. These may be used alone or in combination of two or more. In one embodiment, lithium hydroxide may be used as the lithium source.
[0084] In some embodiments, a source containing the aforementioned auxiliary elements (eg, hydroxide or oxide) may also be used together.
[0085] According to some embodiments, impurities such as LiOH and Li2CO3 may remain on the surface of the lithium transition metal oxide particles. The impurities can be removed by washing with water or organic solvents.
[0086] In one embodiment, a post-firing process may be further performed after the cleaning process. The post-firing process may be performed at a temperature of about 250 to 500° C. Through the post-firing process, the doping stability of strontium and sulfur may be enhanced.
[0087] <Lithium Secondary Battery>
[0088] Figure 1 and Figure 2 1 and 2 are schematic plan views and cross-sectional views of a lithium secondary battery according to an exemplary embodiment. Figure 2 is along Figure 1 Cross-sectional view taken along line I-I' in the thickness direction.
[0089] Figure 1 and Figure 2 The structure shown is exemplified for the convenience of explanation, and the structure of the lithium secondary battery according to the embodiment of the present disclosure is not limited thereto.
[0090] refer to Figure 1 and Figure 2 The lithium secondary battery may include an electrode assembly including a positive electrode 100, a negative electrode 130, and a separator 140 interposed therebetween. The electrode assembly may be accommodated in a case 160 together with an electrolyte to be impregnated.
[0091] The positive electrode 100 may include a positive active material layer 110 formed by coating a positive active material onto a positive current collector 105. The positive active material may include a compound capable of reversibly inserting and deinserting lithium ions.
[0092] In an exemplary embodiment, the positive electrode active material may include the lithium transition metal oxide. The slurry is prepared by mixing and stirring the positive electrode active material with a binder, a conductive material and / or a dispersing material in a solvent. The slurry may be coated on the positive electrode current collector 105 and then dried and compressed to manufacture the positive electrode 100.
[0093] The positive electrode current collector 105 may include, for example, stainless steel, nickel, aluminum, titanium, copper, or alloys thereof. The positive electrode current collector 105 may include aluminum or an aluminum alloy.
[0094] The above-mentioned adhesive may include organic adhesives such as polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile (polyacrylonitrile), polymethyl methacrylate (polymethylmethacrylate) or water-based adhesives such as styrene-butadiene rubber (SBR), and may be used together with a thickener such as carboxymethyl cellulose (CMC).
[0095] For example, a PVDF-based binder can be used as the positive electrode binder. In this case, the amount of the binder used to form the positive electrode active material layer can be reduced, and the amount of the positive electrode active material can be relatively increased, thereby improving the power and capacity of the secondary battery.
[0096] The above conductive materials may be included to promote electron migration between active material particles. For example, the above conductive materials may include carbon-based conductive materials such as graphite, carbon black, graphene, and carbon nanotubes and / or metal-based conductive materials such as perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, and LaSrMnO3.
[0097] The negative electrode 130 includes a negative electrode current collector 125 and a negative electrode active material, and may include a negative electrode active material layer 120 formed on the negative electrode current collector 125.
[0098] According to an exemplary embodiment, the above-mentioned negative electrode active material may include a silicon-based active material. For example, the above-mentioned negative electrode active material may include Si, SiO x (0 < x < 2), silicon-carbon composite, metal-doped silicate, or SiOx (0 < x < 2), etc.
[0099] The above-mentioned silicon-based active material can provide, for example, a significantly increased capacity compared to carbon-based materials. However, the above-mentioned silicon-based active material expands excessively in a high-temperature environment or during repeated charge / discharge, which may lead to deterioration of battery stability.
[0100] Therefore, a carbon-based active material can be used together with the silicon-based active material as the above-mentioned negative electrode active material. The above-mentioned carbon-based active material may include crystalline carbon, amorphous carbon, carbon composite, carbon fiber, etc.
[0101] For example, the above-mentioned amorphous carbon may include hard carbon, coke, mesophase carbon microspheres, mesophase pitch-based carbon fiber, etc. For example, the above-mentioned crystalline carbon may include natural graphite, artificial graphite, graphitized coke, graphitized MCMB, graphitized MPCF, etc.
[0102] In one embodiment, natural graphite and / or artificial graphite can be used as the carbon-based active material.
[0103] To prevent instability caused by battery expansion, the amount of the above-mentioned carbon-based active material (e.g., graphite-based active material) in the total weight of the above-mentioned negative electrode active material may be greater than the amount of the silicon-based active material.
[0104] According to an exemplary embodiment, in the total weight of carbon element (C) and silicon element (Si) contained in the above-mentioned negative electrode active material, the weight ratio of the silicon element may be 1% to 10%. Within the above range, according to the high-capacity / high-stability design of the above-mentioned positive electrode, the negative electrode can also provide a high-capacity / high-stability structure.
[0105] In some embodiments, the weight ratio of silicon element in the negative electrode active material may be 1% to 9%, 1% to 8%, 1% to 7%, 1% to 6%, or 1% to 5%.
[0106] For example, the above-mentioned negative electrode active material can be mixed and stirred together with the above-mentioned binder, conductive material, thickener, etc. in a solvent to prepare a slurry. The above-mentioned slurry can be coated on at least one surface of the negative electrode current collector 125, and then compressed and dried to manufacture the negative electrode 130.
[0107] As the above-mentioned binder and conductive material, materials substantially the same as or similar to those used in the positive electrode active material layer 110 can be used. In some embodiments, the binder used to form the negative electrode may include, for example, an aqueous binder such as styrene-butadiene rubber (SBR) for compatibility with the carbon series active material, and may be used together with a thickener such as carboxymethyl cellulose (CMC).
[0108] A separator 140 may be provided between the positive electrode 100 and the negative electrode 130. The separator 140 may include a porous polymer film made of polyolefin polymers such as ethylene monomer, propylene monomer, ethylene / butene copolymer, ethylene / hexene copolymer, ethylene / methacrylate copolymer, etc. The separator 140 may also include a non-woven fabric formed of high melting point glass fiber, polyethylene terephthalate fiber, etc.
[0109] In some embodiments, the area (eg, the contact area with the separator 140 ) and / or volume of the negative electrode 130 may be larger than that of the positive electrode 100 . Therefore, lithium ions generated from the positive electrode 100 may smoothly move to the negative electrode 130 without being precipitated in the middle.
[0110] According to an exemplary embodiment, an electrode unit is defined by the positive electrode 100, the negative electrode 130 and the separator 140, and a plurality of electrode units may be stacked to form, for example, an electrode assembly 150 in a jelly roll form. For example, the electrode assembly 150 may be formed by winding, laminating, folding, etc., of the separator 140.
[0111] The electrode assembly 150 may be accommodated in the case 160 together with an electrolyte to define a lithium secondary battery. According to an exemplary embodiment, a non-aqueous electrolyte may be used as the electrolyte.
[0112] The non-aqueous electrolyte includes a lithium salt as an electrolyte and an organic solvent. The lithium salt is represented by Li + X - , as the anion of the above lithium salt (X - ), for example, we can list F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF- 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - wait.
[0113] As the above-mentioned organic solvent, for example, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, ethylene carbonate, cyclopentane sulfone, γ-butyrolactone, propylene sulfite and tetrahydrofuran can be used. These can be used alone or in combination of two or more.
[0114] like Figure 1 As shown, electrode tabs (positive electrode tabs and negative electrode tabs) may protrude from the positive electrode collector 105 and the negative electrode collector 125 belonging to each electrode unit and extend to one side of the housing 160. The electrode tabs may be fused with the one side of the housing 160 and connected to electrode leads (positive electrode lead 107 and negative electrode lead 127) extending or exposed to the outside of the housing 160.
[0115] The lithium secondary battery may be manufactured in a cylindrical, square, pouch, or coin shape using a can, for example.
[0116] The following preferred embodiments are provided to help understand the present disclosure, but these embodiments are merely illustrative of the present disclosure and do not limit the scope of the appended claims. It is obvious to a person skilled in the art that various changes and modifications can be made to the embodiments within the scope of the present disclosure and the technical concept, and it is natural that these changes and modifications belong to the scope of the appended claims.
[0117] Examples and Comparative Examples
[0118] (1) Manufacturing positive electrode
[0119] Example 1
[0120] NiSO4, CoSO4 and MnSO4 were mixed into the composition shown in Table 1 using distilled water that was bubbled with N2 for 24 hours to remove dissolved oxygen. The above solution was placed in a reactor at 60°C, and a coprecipitation reaction was performed for 48 hours using NaOH and NH3H2O as a precipitant and a chelating agent, respectively. After the coprecipitation reaction, the reactants were separated by a centrifuge to remove impurities, and then the precipitate was washed with distilled water for about 5 times to prepare an active material precursor whose S content was adjusted to a range of about 1500 to 3000 ppm.
[0121] Sr(OH)2 as a strontium source and LiOH as a lithium source were further mixed to the composition shown in Table 1 below, and calcined in a calcination furnace at 710°C to obtain a positive electrode active material containing lithium nickel composite metal oxide particles. The S content was adjusted as shown in Table 1 below by the above calcination.
[0122] Example 2
[0123] The precursor was prepared in the same manner as in Example 1 except that the precursor was washed approximately twice with 1% HCl added to distilled water at a ratio of 100:1 and then washed approximately 10 times with distilled water to adjust the S content to less than 500 ppm.
[0124] Then, Sr(OH)2 as a strontium source, LiOH as a lithium source, (NH4)2SO4 and Al(OH)3 were further mixed to the composition shown in the following Table 1, and sintered at 710°C in a sintering furnace to obtain a positive electrode active material containing lithium nickel composite metal oxide particles.
[0125] Example 3
[0126] The precursor and active material were prepared in the same manner as in Example 1, except that NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed into the composition shown in Table 1 when preparing the precursor.
[0127] Example 4
[0128] The precursor and active material were prepared in the same manner as in Example 1, except that Sr(OH)2 and Al(OH)3 were added to the lithium source to obtain the composition shown in Table 1.
[0129] Example 5
[0130] The precursor and active material were prepared by the same method as in Example 1, except that NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed to the composition shown in Table 1 to form the precursor, and Sr(OH)2 and Al(OH)3 were further added when mixing the lithium source.
[0131] Embodiment 6, 8
[0132] The same procedure as in Example 3 was followed except that NiSO 4 , CoSO 4 and MnSO 4 were mixed to a composition shown in Table 1 when preparing the precursor.
[0133] Embodiment 7, 9
[0134] The same procedure as in Example 2 was followed except that NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed to a composition shown in Table 1 when preparing the precursor.
[0135] Comparative Example 1
[0136] The same procedure as in Example 3 was followed except that NiSO 4 , CoSO 4 and MnSO 4 were mixed to a composition shown in Table 1 when preparing the precursor.
[0137] Comparative Example 2
[0138] The same procedure as in Example 2 was followed except that (NH4)2SO4 was not added when mixing the lithium source.
[0139] Comparative Example 3
[0140] The same procedure as in Example 2 was followed except that Sr(OH)2 and (NH4)2SO4 were not added when mixing the lithium source.
[0141] Comparative Example 4
[0142] The same procedure as in Example 2 was followed except that NiSO4, CoSO4 and MnSO4 were mixed to a composition shown in Table 1 to generate the precursor and (NH4)2SO4 was not added when mixing the lithium source.
[0143] Specifically, the content of each component of the positive electrode active material was measured by inductively coupled plasma (ICP), converted into moles, and recorded in the following Table 1.
[0144] The above positive electrode active material, Denka Black as a conductive material, and PVDF as a binder were mixed at a mass ratio of 92:5:3 to prepare a positive electrode mixture, which was then coated on an aluminum current collector, and then a positive electrode was manufactured by drying and pressing.
[0145] (2) Manufacturing of negative electrodes and secondary batteries
[0146] The graphite-based negative electrode active material and the silicon-based negative electrode active material (SiOx, 0 < x < 2) were mixed so that the weight ratio of silicon to carbon analyzed by ICP was 1:99 to prepare the negative electrode active material.
[0147] The above negative electrode active material, flake type conductive material KS6, and binder styrene-butadiene rubber (SBR) were mixed at a weight ratio of 94:0.9:3 to prepare a negative electrode slurry. The above negative electrode slurry was coated on a copper substrate and dried and pressed to manufacture a negative electrode.
[0148] The positive electrode and the negative electrode manufactured as above were respectively notched into predetermined sizes, and a separator (polyethylene, thickness 25 μm) was disposed between the above positive electrode and the negative electrode to stack them. The tab portions of the positive electrode and the negative electrode were respectively welded. The welded positive electrode / separator / negative electrode assembly was placed in a bag and three sides other than the electrolyte injection surface were sealed. The portion with the electrode tab was included in the sealed portion. The electrolyte was injected through the electrolyte injection surface, and after the electrolyte injection surface was also sealed, it was impregnated for more than 12 hours.
[0149] As the electrolyte, a 1M LiPF6 solution using a mixed solvent of EC / EMC / DEC (25 / 45 / 30; volume ratio) was adopted. 1 wt% of ethylene carbonate (VC), 0.5 wt% of 1,3-propane sultone (PRS), and 0.5 wt% of lithium bis(oxalate)borate (LiBOB) were added to the above electrolyte.
[0150] Thereafter, pre-charging was performed at a current equivalent to 0.25C (5A) for 36 minutes. One hour later, degassing and aging for more than 24 hours were performed, and then formation charge and discharge (charging condition CC-CV 0.2C 4.2V 0.05C cut-off (CUT-OFF), discharging condition CC 0.2C 2.5V cut-off (CUT-OFF)) were performed. Thereafter, standard charge and discharge (charging condition CC-CV 0.5C 4.2V 0.05C cut-off (CUT-OFF), discharging condition CC 0.5C 2.5V cut-off (CUT-OFF)) was performed at 35°C.
[0151]
Table 1
[0152]
[0153] Experimental example
[0154] (1) Measuring capacity retention
[0155] The lithium secondary batteries according to Examples and Comparative Examples were repeatedly charged (CC / CV 0.5C 4.3V 0.05C CUT-OFF) and discharged (CC 1.0C 3.0V CUT-OFF) for 5000 cycles at 45°C, and the discharge capacity retention was evaluated as a percentage of the value of the discharge capacity after 5000 cycles divided by the primary discharge capacity.
[0156] (2) Measuring gas generation
[0157] The lithium secondary batteries of Examples and Comparative Examples were stored in a chamber at 60° C. after repeated charge / discharge for 5000 cycles. After 16 weeks of storage, the lithium secondary batteries were taken out of the chamber and the amount of gas generated was analyzed by gas chromatography.
[0158] The evaluation results are shown in Table 2 below.
[0159]
Table 2
[0160] Co / Mn Sr / S Capacity retention rate (%) Gas production (ml) Example 1 1.0 0.6 94.6 48 Example 2 1.2 0.2 96.6 24 Example 3 1.2 0.6 94.2 57 Example 4 1.2 1.7 96.4 29 Example 5 1.5 2.1 94.0 50 Example 6 1.0 1.6 91.4 67 Example 7 1.0 0.1 89.4 64 Example 8 0.9 1.3 81.2 115 Example 9 0.9 0.1 79.6 108 Comparative Example 1 3.5 0.7 93.0 63 Comparative Example 2 1.1 4.5 86.4 91 Comparative Example 3 1.2 - 89.5 104 Comparative Example 4 1.0 4.8 63.4 294
[0161] (3)DSC analysis
[0162] In order to evaluate the thermal characteristics of the positive electrode active materials of Examples 1 and 2 and Comparative Example 1, the exothermic peak temperature and the calorific value were measured using differential scanning calorimetry (DSC).
[0163] The evaluation results are shown in Table 3 below.
[0164]
Table 3
[0165]
[0166] Referring to Table 2, in the examples where the Co / Mn ratio was 0.9 to 1.5 and the Sr / S ratio was 4 or less, a stable capacity retention rate was provided even in the case of 5000 cycles of repeated charge / discharge, and gas generation was suppressed under high temperature conditions.
[0167] Figure 3 It is a differential scanning calorimetry (DSC) analysis chart of the positive electrode active material particles of Examples 1 and 2 and Comparative Example 1.
[0168] See also Figure 3As shown in Table 3, the exothermic peaks of the positive electrode active materials of Examples 1 and 2 shifted to higher temperatures, showing lower calorific value, compared with Comparative Example 1. It can be predicted that by adjusting the Co / Mn ratio and the Sr / S ratio at the same time, thermal stability is also improved.
[0169] (4) Evaluation of the capacity retention rate according to the silicon ratio of the negative electrode active material
[0170] Secondary batteries were manufactured in the same manner as in Example 1, except that the weight ratio of silicon in the negative electrode active material was increased to 5 wt % (Example 10), 7 wt % (Example 11), and 12 wt % (Example 12).
[0171] Thereafter, the capacity retention ratios of the secondary batteries according to Examples 10 to 12 were measured by the same method as in (1).
[0172] The measurement results are shown in Table 4 below.
[0173]
Table 4
[0174]
[0175] As the Si content in the negative electrode active material increases, the capacity of the secondary battery can be further increased by combining it with the positive electrode active material. However, in reference to Example 12, when the Si content exceeds 10 wt %, the capacity retention rate decreases relatively.
Claims
1. A positive electrode active material for a lithium secondary battery, comprising: A lithium transition metal oxide containing nickel (Ni), cobalt (Co), manganese (Mn), strontium (Sr), and sulfur (S), In the lithium transition metal oxide, the molar fraction of nickel in the total molar amount of nickel, cobalt, and manganese is 0.9 or more, In the lithium transition metal oxide, the molar ratio of cobalt to manganese is 0.9 to 1.5, In the lithium transition metal oxide, the molar ratio of strontium (Sr) to sulfur (S) is greater than 0 and 4 or less.
2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein in the lithium transition metal oxide, the molar ratio of cobalt to manganese is 1 to 1.
5.
3. The positive electrode active material for a lithium secondary battery according to claim 1, wherein in the lithium transition metal oxide, the molar ratio of strontium (Sr) to sulfur (S) is 0.1 to 3.
4. The positive electrode active material for a lithium secondary battery according to claim 1, wherein in the lithium transition metal oxide, the content of nickel among the elements other than lithium and oxygen is 90% or more.
5. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the lithium transition metal oxide further contains Al.
6. The positive electrode active material for a lithium secondary battery according to claim 5, wherein the content of Al in the total weight of the lithium transition metal oxide is 1000 ppm to 10000 ppm.
7. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the lithium transition metal oxide includes a layered structure or a crystal structure represented by Chemical Formula 1: [Chemical Formula 1] Li a Sr b (Ni x M1 1-x) M2 y O 2-z S z In Chemical Formula 1, 0.95 ≤ a + b ≤ 1.1, 0 < b ≤ 0.1, 0.9 < x < 1.0, 0 ≤ y ≤ 0.1, 0 < z ≤ 0.1, M1 includes Co and Mn, and M2 is a foreign metal other than Ni, Co, Mn, and Sr.
8. The positive electrode active material for a lithium secondary battery according to claim 7, wherein in Chemical Formula 1, M2 includes at least one selected from Al, Rb, Y, Zr, Nb, Mo, Ru, Ag, Sn, and Sb.
9. A lithium secondary battery, comprising: A positive electrode including the positive electrode active material for a lithium secondary battery according to claim 1; And A negative electrode opposite to the positive electrode, including a negative electrode active material containing a carbon-based active material and a silicon-based active material.
10. The lithium secondary battery according to claim 9, wherein in the total weight of carbon element (C) and silicon element (Si) contained in the negative electrode active material, the weight ratio of the silicon element is 1% to 10%.
11. The lithium secondary battery according to claim 9, wherein in the total weight of carbon element (C) and silicon element (Si) contained in the negative electrode active material, the weight ratio of the silicon element is 1% to 7%.
12. The lithium secondary battery according to claim 9, wherein the carbon-based active material includes natural graphite or artificial graphite.